PELATIHAN MENYIMAK CERITA MELALUI MEDIA AUDIO VISUAL PADA SISWA TK CINTA DAMAI RSS. SRIWIJAYA OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
This service is motivated by the problems faced bystudents in learning tolisten to stories, so that students feelbored and lazy to take part in learning, as a result learning out comes decline .This dedication aims to improve students' ability to listen to a story through the application of audio-visual media. The method of implementing activities includes 3 stages,namely the preparation stage, the activity implementation stage, and the evaluation stage. The target of this training activity is the 3rd grade students of TK Cinta Damai RSS Sriwijaya OKU. Theresults of the implementation of this service activity are students who understand more quickly ,are motivated and active in participating in story listening learning activities, students who get scores above the minimum completeness criteria increase to50%, previously only 25% of the total number of students, the ability to listen to stories in students experiences improvement, this is evidenced from seeing the results of evaluation tests that were answered well by students.